AN ANALYSIS POLITENESS STRATEGIES IN THE DIRECTIVE UTTERED BY CHARACTERS IN BIG HERO 6 MOVIE - Ilham Muhammad Nur; Rusdi Noor Rosa (English Language and Literature, 2019)
This research studies about directive speech acts in Big Hero 6 movie. The objectives of this research are to know the kinds of directive speech acts and the kinds of politeness strategies. The researcher takes the data from the movie entitled Big Hero 6. This research is a qualitative research by employing descriptive method. The result tends to focus on the deep meaning of the dialogue’s quality rather than the quantity of number. The data of this research are taken from directive speech acts in dialogues in the movie. The instrument of this research is the reseacher herself who collects, analyzes, and presents the data findings of the researchthen draw the conclusion. The researcher applied the trustworthiness of the data to obtain the valid data. The result of the analysis shows four kinds of directive speech acts uttered in Big Hero 6 movie. There are 34 data (42.5%) belongs to ordering,21 data (26.25%) belong to request,20 data  (25%) belong to asking,5 data (6.25%) belong to suggesting. The kinds of politeness strategies in Big Hero 6 movie are positive politeness strategy and bald on record strategy. There are 26 data (32.5%) belongs to the positive politeness strategy,54 data (67.5%) belong to bald on record strategy.